The role of sialidases in the pathogenesis of bacterial vaginosis and their use as a promising pharmacological target in bacterial vaginosis - Chen, Liuyan; Li, Jiayue; Xiao, Bingbing (Frontiers in Cellular and Infection Microbiology, 2024)
Bacterial vaginosis (BV) is an infection of the genital tract characterized by disturbance of the normally Lactobacilli-dominated vaginal flora due to the overgrowth of Gardnerella and other anaerobic bacteria. Gardnerella vaginalis, an anaerobic pathogen and the major pathogen of BV, produces sialidases that cleave terminal sialic acid residues off of human glycans. By desialylation, sialidases not only alter the function of sialic acid-containing glycoconjugates but also play a vital role in the attachment, colonization and spread of many other vaginal pathogens. With known pathogenic effects, excellent performance of sialidase-based diagnostic tests, and promising therapeutic potentials of sialidase inhibitors, sialidases could be used as a biomarker of BV. This review explores the sources of sialidases and their role in vaginal dysbiosis, in aims to better understand their participation in the pathogenesis of BV and their value in the diagnosis and treatment of BV.